â€œSLIDE-FORWARD RECESSIONâ€ : EINSTEINâ€™S MAIN FINDING PROVES EVEN STRONGER - Rossler, Otto E. (European Scientific Journal, ESJ, 2015)
The oldest gravitational ideaof Einstein is by the use of a toy model shown to be still more powerful: It implies c-global. This new fact if true is decisive for the unification of physics. Remember how Einstein predicted gravitational redshift â€“ the fact that our clocks tick slower than those in the satellites overhead â€“ ? He invented the toy model of a constantly accelerating long rocketship in outer space, Jules-Verne style.